SYIRKAH SEBAGAI MODEL INVESTASI BERBASIS SYARI’AH (KAJIAN ONTOLOGI) - Dyah Ochtorina Susanti (Tribakti: Jurnal Pemikiran Keislaman, 2013)
The aim of this reseach is discover and analyze and give an evaluation about the concept of syirkah in Indonesian positive law. Syirkah is a mixture capital between two or more people who aim to create a partnership in a particular field. The results of studies which is using the method of normative juridical approach, statute approach, and legal history was made ​​clear that syirkah has been arranged in the positive law in Indonesia in the frame of banking law. The presence of syirkah concept in banking law is driven by the desire of Muslims to apply the teachings mu'amalah